Answer:
19.685
Step-by-step explanation:
Answer:
x≤ −2/3y + −1/3
Step-by-step explanation:
because...
Step 1: Add -4y to both sides.
6x + 4y + −4y ≤ −2+−4y
6x ≤ −4y −2
Step 2: Divide both sides by 6.
6x/6 ≤
x ≤ −2/3y + −1/3
Therefor, the answer is x≤ −2/3y + −1/3
* Hopefully this helps:) Mark me the brainliest:)!!
33x I think sorry if I am wrong
C !.!.!!.!..!.!!.!.!.!.!.!.!.!.!.!.!.!.!.!.!.!.!.!
Answer:
7/12
Step-by-step explanation:
7/6 - (1/4 + 1/3) =
7/6 - 1/4 - 1/3 = 14/12 - 3/12 - 4/12 = 7/12